Peer To Peer Market Management And Policy Modeling Of The Electricity Market. (May 2022) - Liu, Ying; Liao, Qi
Highlights: Energy flow in the IES to decrease the costs of lines reconstructing and the grid impact of bidirectional energy flow. The scheduling has adjusted the flexible cold, heat, and electric loads applying the demand response approach. Carbon emissions control of multi-energy resources Abstract: This paper proposes a novel multi-energy system (MES) by establishing an energy hub (EH) that includes an integrated electric vehicle and energy storage system. An optimal scheduling scheme is proposed to minimize the purchasing costs and emission values, so-called near zero-sum emission, in MES. The present study concludes by comparing the economic benefits of the fixed and response modes and discussing the role of the energy storage device and multi-energy complementary mode in maximizing energy performance. To solve the optimization problem, whale optimization algorithm is applied. According to the simulation outcomes, the optimal scheduling approach of the EH is capable of coordinating between different complementary energy modes quite well. Additionally, the suggested approach improves the operating performance of the EH and ensures better demand response. The sensitivity analysis illustrates that a small change in pollutant emission prices affects emission reductions effectively. Graphical abstract: Image, graphical abstract